A Usage‐Based Approach to Preposition Placement in English as a Second Language. Issue 1 (20th December 2017) - Jach, Daniel
Abstract: This study examined the acquisition of preposition placement in English as a second language from a usage‐based perspective. German and Chinese learners of English and English native speakers rated the acceptability of English oblique wh relative clauses in a magnitude estimation task. Results indicated that acceptability depended on interactions among preposition fronting and stranding, participant group, participants' first language, and their English proficiency. Most importantly, while stranding was more acceptable than fronting across learner groups, fronting was more acceptable to German than to Chinese learners of English. In line with the usage‐based approach, input frequency and crosslinguistic similarity appeared to have a significant influence on the acquisition of preposition fronting and stranding in English. These findings are discussed in light of prior usage‐based studies pointing to the role of input frequency and similarity in language acquisition as well as in light of recent research on construction learning across languages.